Serbia Judicial Functional Review - World Bank Group (Washington, DC, 2015)
This functional review presents a comprehensive assessment of the current functioning of Serbia's judicial system, along with options and recommendations to inform Serbia's justice reform initiatives in view of the requirements of Chapter 23 of the Acquis Communautaire. The review comprises an external performance assessment and an internal performance assessment. The external performance assessment (Part 1) examines how well the Serbian judicial system serves its citizens in terms of efficiency, quality, and access to justice services. The internal performance assessment (Part 2) examines the inner workings of the system, and how governance and management, financial and human resources, ICT, and infrastructure are managed for service delivery. A distinct feature of this Review is its emphasis on data and analysis. The data collection was undertaken in the first half of 2014, and the preliminary findings were discussed with stakeholders and international partners through July, August and September of 2014. Overall, Serbia's judicial system performs at a lower standard than that of EU Member States. Of the many findings and recommendations outlined in the Report, the Functional Review team suggests that leaders focus on the following seven priorities which can set the Serbian judiciary on a critical path to performance improvement: 1) Develop a performance framework that tracks the performance of courts and PPOs against a targeted list of key performance indicators; 2) Ensure that courts use the full functionality of their case management systems to improve consistency of practice and support evidence-based decision-making; 3) Develop a comprehensive continuing training program for judges, prosecutors and court staff; 4) Reform procedural laws to simplify the service of process, and start simplifying business processes; 5) Eliminate the backlog of old utility bill enforcement cases; 6) Develop a more realistic budget within the existing resource envelope; and 7) Adjust the resource mix over time by gradually reducing the wage bill and increasing investments in productivity and innovation. This report was funded by the Multi-Donor Trust Fund for Justice Sector Support in Serbia (MDTF-JSS).